\frac { - 3x } { 7} - \frac { 4} { 5} = \frac { - 10x + 15} { 5}
Take terms with variable x on one side:
=> - \frac { 4} { 5} = \frac { - 10x + 15} { 5} - \frac { - 3x } { 7}
To evaluate right hand side, we need to have equal denominators:
=> - \frac { 4} { 5} = \frac { - 10x + 15} { 5} (7/7)- \frac { - 3x } { 7}(5/5)
=> - \frac { 4} { 5} = \frac { - 70x + 105} { 35} + \frac { 15x } { 35}
=> - \frac { 4} { 5} = \frac { - 70x +15x + 105} { 35}
=> - \frac { 4} { 5} = \frac { - 55x + 105} { 35}
=> - \frac { 4} { 5} xx 35 = \frac { - 55x + 105} { 1} ......transpose
=> - \frac {4}{cancel5} xx cancel35^7=\frac{-55x +105}{1}
=> -28 = -55x +105
=> 55x = 105 + 28
=> x = 133/55
therefore x = 2 23/55